Conversion of commercial Pt/C to "clean" Pt-Cu/C catalyst with high activity toward methanol oxidation. (1st December 2015) - Liu, Hongmei; Wang, Shengqing; Jia, Falong
ABSTRACT: A green synthetic strategy is developed to prepare Ptx Cuy /C catalyst in the absence of any capping ligands. Commercial Pt/C catalyst is used as the platinum precursor, and the Pt nanoparticles on the carbon act as a catalyst for the reduction of copper (II) precursors by hydrazine, which leads to the confined deposition of Cu on the Pt nanoparticles. The newly deposited Cu diffuses into the Pt nanoparticles to form Ptx Cuy alloy nanoparticles under hydrothermal conditions. The as-synthesized Ptx Cuy /C exhibits superior activity compared with commercial Pt/C towards the electro-oxidation of methanol. The results highlight the significance of alloy formation as an approach to improve the activity of commercial Pt/C catalyst.